Playing tennis in hot environment: Applied strategies and new directions - Robin, N.; Dominique, L.; Coudevylle, G. R. (Coaching and Sport Science Review, 2021)
Many tennis competitions are held in hot ambient conditions, which can negatively affect endurance, mental and cognitive functioning and/or motor performance. The purpose of this article is to take stock of the physical techniques and psychological strategies that tennis players can use to counteract the negative effect of the heat. In addition, a new direction based on the mindfulness technic is proposed in this article.